MENANGKAL PENYEBARAN HOAKS DAN DISINFORMASI DI DUNIA DIGITAL - Bawazir Fadhil Mohammad; Ahmad Wildan Amrullah; Taufikurrahman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The development of information and communication technology has brought us into the digital era, where information can spread quickly and widely. This progress provides many advantages, such as easy access to information and increased social interaction. However, the digital environment also presents major challenges in the form of the spread of hoaxes and disinformation. This false information not only confuses the public, but can also have negative impacts, such as damaging public trust, triggering social unrest, and even influencing political decisions. This article aims to provide a comprehensive review of the spread of hoaxes and disinformation in the digital world. One of the main factors driving its spread is the low level of digital literacy among the public. In addition, social media algorithms that prioritize sensational content and economic motives behind the spread of fake news are also significant driving factors. Through literature analysis and case studies, this article emphasizes the importance of digital literacy, regulation, and cross-sector collaboration. Individuals, society, government, and digital platforms must work together to combat this phenomenon.